Limites à discricionariedade do Ministério Público no oferecimento do acordo de não persecução penal - Siqueira, Ana Beatriz Barros de (2024)
Consensual or negotiated criminal justice has been adopted by several countries since the end of the 20th century. It is not an isolated experience, but a global phenomenon, which encompasses States with common law and civil law traditions, in accordance with the particularities of each legal system. Although the existence of this model of justice is criticized, the current state of affairs shows the consolidation of the scenario of consensus and negotiation in the criminal sphere, so the search for an understanding of consensual institutes according to Federal Constitution is meaningful. From this perspective, the non-prosecution agreement (NPA) can be seen as a benefit to the defendant, notably because it allows the elimination of the possibility of punishment. Thus, the study about the refusal of the Public Prosecutor to offer the agreement is relevant, since it will prevent the defendant from obtaining a benefit for himself. In this context, the aim of this research is to identify the limits to the Public Prosecutor's discretion in deciding whether or not to offer a NPA. With this purpose, this resarch intends to answer the following question: what means can be useful in limiting the discretion of the Public Prosecutor regarding the choice of wheter or not to offer a proposal for a NPA? Therefore, initially, the essential aspects for understanding the NPA, as the most recent consensual mechanism incorporated into the Brazilian legal system, are presented. This is followed by an analysis of the relevant topics surrounding the prosecutor’s offer of a NPA. Finally, limits are establish on the discretion of the Public Prosecutor's Office in choosing whether or not to offer an NPA. The research presents a qualitative approach and is characterized mainly as exploratory, using as techniques the documentary and bibliographical analysis. The conclusion is that the following are useful means of limiting the Public Prosecutor's discretion as to whether or not to offer a NPA: i) internal control within the Public Prosecutor's Office, as provided for in article 28-A, §14, of the Brazilian Code of Criminal Procedure; ii) judicial control over the legality of the refusal, notably by the rejection of the criminal charge; iii) the inadmissibility of the Public Prosecutor's Office creating abstract prohibitions on offering the NPA.